a STRATEGI KOMUNIKASI BADAN NARKOTIKA KABUPATEN DALAM PENANGGULANGAN BAHAYA NARKOBA DI KABUPATEN KLUNGKUNG: Strategi Komunikasi - I Nyoman Tangkas; I Dewa Ayu Hendrawathy Putri; I Gede Januariawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
Communication is an important aspect in campaigning for the impact of drug abuse on society. To carry out these communication activities, a strong and effective communication strategy is needed by the BNN (National Narcotics Agency) institution or agency so that the intended message can be conveyed to the target community. The type of research used is qualitative, namely describing and analyzing the data that has been obtained and then elaborated in the form of an actual explanation, to find out the strategy of the District National Narcotics Agency in reducing the level of Narcotics users. The purpose of this research is to find out the dangers of drug abuse and the steps taken by the Klungkung BNNK to involve the Traditional Village in preventing drug trafficking in Klungkung Regency. The strategy carried out by the BNN (National Narcotics Agency) of Klungkung Regency in order to prevent drug abuse is to implement a program of drug abuse prevention activities, which consists of advocacy and information dissemination and by involving the role of traditional leaders to include drug abuse rules into the “Pararem” of the Traditional Village. “Pararem” is the rule or decision of the Traditional Village meeting as the implementation of the Law in the Traditional Village which regulates new matters in solving a new problem related to traditional cases in a Traditional Village. Efforts made by the National Narcotics Agency of Klungkung Regency to include “Pararem” in Traditional Villages related to the dangers of drugs in Klungkung Regency Increase Cooperation with the Majelis Desa Adat Kabupaten Klungkung, Dissemination of Information on Prevention and Community Empowerment Programs to be included in the “Pararem” of Traditional Villages and Formation of a drug free village.